Experimental Characterization of Phase Change Materials for Refrigeration Processes - Anastasia Stamatiou; Lukas Müller; Roger Zimmermann; Jamie Hillis; David Oliver; Kate Fisher; Maurizio Zaglio; Jörg Worlitschek (Energies, 2021)
Latent heat storage units for refrigeration processes are promising as alternatives to water/glycol-based storage due to their significantly higher energy densities, which would lead to more compact and potentially more cost-effective storages. In this study, important thermophysical properties of five phase change material (PCM) candidates are determined in the temperature range between −22 and −35 °C and their compatibility with relevant metals and polymers is investigated. The goal is to complement existing scattered information in literature and to apply a consistent testing methodology to all PCMs, to enable a more reliable comparison between them. More specifically, the enthalpy of fusion, melting point, density, compatibility with aluminum, copper, polyethylene (PE), polypropylene (PP), neoprene and butyl rubber, are experimentally determined for 1-heptanol, n-decane, propionic acid, NaCl/water mixtures, and Al(NO3)3/water mixtures. The results of the investigations reveal individual strengths and weaknesses of the five candidates. Further, 23.3 wt.% NaCl in water stands out for its very high volumetric energy density and n-decane follows with a lower energy density but better compatibility with surrounding materials and supercooling performance. The importance of using consistent methodologies to determine thermophysical properties when the goal is to compare PCM performance is highlighted.